The Efficacy Of Mall Instruction In Tourism English Learning During Covid-19 Pandemic - I Putu Edi Sutrisna; Pradna Lagatama; Nyoman Dane (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2020)
The Efficacy of MALL Instruction in Tourism English Learning during COVID-19 Pandemic. Present study was a descriptive qualitative research aiming at finding the deeper insight about this the efficacy of Mobile Assisted Language Learning (MALL) instruction in English learning during COVID 19 pandemic from the point of view of the lecturers at Hinduism Cultural Tourism Study Program of STAHN Mpu Kuturan Singaraja. Specifically, the objectives of this study were to find out what language teaching activities that the students do in MALL based instructions; and to find out the effectiveness of MALL based instructions during COVID-19 pandemic from the lecturers’ point of view. To ensure the validity of the data collected, this present study used the method of data triangulation by obtaining data from the main informant and being reviewed with the data collected from two secondary informants. As informants for the present analysis, three English lecturers were selected. The first informants were established as primary informants and the other two informants were listed as secondary informants. To collect the data from the informants, the Interview Guide was used. This interview guide was checked by two expert judges using face validity, resulting in a credible and ready-to-use interview guide as the study tool. The Miles & Huberman (1984) Interactive Data Analysis Model was used to analyze the data. Then, as the research methodology carried out, it was found that several categories of teaching activities by using Mobile Assisted Language Learning including the activities of listening, speaking, reading, and writing. Those English competences were taught by the lectures by utilizing mobile phone application so then the students could be able to master the target language anytime and anywhere. Specifically, by using Mobile Assisted Language Learning, the lecturers could provide teaching activities management, video conference teaching and learning activities, and sharing teaching materials (e-books, audio, and video). It was also found that the lecturers perceived that Mobile Assisted Language Learning (MALL) was beneficial during COVID-19 pandemic. It was because this MALL could give a better assistance to the lecturers as well as the students who could not be able to have a regular face-to-face classroom meeting. By using this Mobile Assisted Language Learning, the students and the lecturers could have an artificial classroom that they can interact each other. However, from this study, it was found that it there were many potentials of Mobile Assisted Language Learning which could not be optimized yet in the English instructional process occurred in Hinduism Cultural Tourism Study Program of STAHN Mpu Kuturan Singaraja. Those limitations mostly came from the lecturers’ side, who were not ready in preparing a sophisticated Mobile Assisted Language instructions. Keywords: Mobile assisted language learning, tourism English